Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/pds.1527
|View full text |Cite
|
Sign up to set email alerts
|

Use of herbal drugs during early pregnancy in relation to maternal characteristics and pregnancy outcome

Abstract: The most commonly reported herbal drugs used during pregnancy were Floradix (iron-rich herbs), ginseng and valerian. No signs of unfavourable effect on pregnancy outcome were seen. The number of exposures, however, was low and therefore effects on rare outcomes (e.g. specific malformations) cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 27 publications
4
47
0
1
Order By: Relevance
“…Therefore, there was no convincing evidence that KRGE administration would cause embryo-fetal toxicity in mice. In contrast to previous in vitro findings that suggested ginseng can be teratogenic (Chan et al, 2003(Chan et al, , 2004Liu et al, 2005Liu et al, , 2006, our results are in agreement with previous reports that showed the use of herbal medicine including ginseng did not cause abnormalities during pregnancy in human (Holst et al, 2008;Seely et al, 2008), suggesting that administration of ginseng has no adverse effects in vivo when used in the range of a maximum-tolerated dose.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Therefore, there was no convincing evidence that KRGE administration would cause embryo-fetal toxicity in mice. In contrast to previous in vitro findings that suggested ginseng can be teratogenic (Chan et al, 2003(Chan et al, , 2004Liu et al, 2005Liu et al, , 2006, our results are in agreement with previous reports that showed the use of herbal medicine including ginseng did not cause abnormalities during pregnancy in human (Holst et al, 2008;Seely et al, 2008), suggesting that administration of ginseng has no adverse effects in vivo when used in the range of a maximum-tolerated dose.…”
Section: Discussionsupporting
confidence: 45%
“…Notably, there is evidence demonstrating the presence of major ginsenosides including Rb1 in the plasma and urine following oral administration (Ji et al, 2004;Tawab et al, 2003), suggesting that these ginsenosides may produce developmental side effects. Although it was reported that the use of ginseng did not exhibit adverse effects on pregnancy outcomes (Holst et al, 2008;Seely et al, 2008), it was not ruled out that, at high concentrations, ginsenosides Rb1, Rg1, and Re could be delivered into the uterus and affect the embryo or fetal development.…”
Section: Introductionmentioning
confidence: 95%
“…Twenty-two articles were screened [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]59 & , 60-62], 16 of them concerning only the use of herbal treatments and six pertaining the employment of complementary alternative medicines (CAM), whereas two [61,62] were excluded from this analysis because of duplicate publications.…”
Section: Most Popular Herbal Remediesmentioning
confidence: 99%
“…There is at least epidemiologic research showing valerian is safe in pregnancy. 30,31 There is no evidence of any negative pharmacokinetic interactions between valerian and any drug. 32 Valerian specifically does not interact with alcohol at doses that definitively interact with benzodiazepines.…”
Section: Moderate Potency Hypnotic Herbsmentioning
confidence: 96%